Traditional Mayan Maternal Health Practices in Guatemala : Reflections from a Maternal Health Pilot in the Department of Sololá, with a Practical Guide to the History, Beliefs, and Cultural Practices of Comadronas in These Communities - Fien-Helfman, Samantha (World Bank, Washington, DC, 2018)
This document offers a useful background for NGOs or organizations working to deliver culturally appropriate maternal health services or interventions through comadronas (midwives) in Sololá, Guatemala or the surrounding region. To this end, the information contained herein focuses on strengthening general awareness and understanding of Mayan culture and promoting the consideration and integration of Mayan maternal health practices and beliefs when designing maternal health trainings or interventions in these communities.